Central-to-Folding Chirality Control: Asymmetric Synthesis of Multilayer 3D Targets With Electron-Deficient Bridges - Jin, Shengzhou; Wang, Jia-Ying; Tang, Yao; Rouh, Hossein; Zhang, Sai; Xu, Ting; Wang, Yu; Yuan, Qingkai; Chen, Daixiang; Unruh, Daniel; Li, Guigen (Frontiers in Chemistry, 2022)
New multilayer 3D chiral molecules have been designed and synthesized asymmetrically through the strategy of center-to-multilayer folding chirality control and double Suzuki couplings. Individual diastereoisomers were readily obtained and separated via flash column chromatography. The key diastereoisomer was further converted into corresponding enantiomers. These enantiomers possess electron-deficient aromatic bridges layered with top and bottom aromatic scaffolds. X-ray structural analysis has unambiguously confirmed the configuration, and intermolecular packing results in regular planar patterns in solid crystals. The synthesis was achieved in a total of ten steps starting from commercially available starting materials.